TRANSFORMASI “ALFU LAILAH WA LAILAH” - Eva Farhah (Arabic Literature Department, 2019)
This research tries to discover and reveal the transformation works from “Alfu Lailah wa Lailah”. The purpose of the discovery and disclosure of the works of transformation is to know the reader's attitude to the work